2008
DOI: 10.1002/hlca.200890180
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemistry of Tetraamminezinc(II) Dipermanganate ([Zn(NH3)4](MnO4)2): Low‐Temperature Synthesis of the Manganese Zinc Oxide (ZnMn2O4) Catalyst Precursor

Abstract: Tetraamminezinc(II) dipermanganate ([Zn(NH 3 ) 4 ](MnO 4 ) 2 ; 1) was prepared, and its structure was elucidated with XRD-Rietveld-refinement and vibrational-spectroscopy methods. Compound 1 has a cubic lattice consisting of a 3D H-bound network built from blocks formed by four MnO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…Taking advantage of the results of our previous investigations [20,[23][24][25][26] and taking into account the results obtained by other researchers [27][28][29][30][31][32][33][34][35][36], the redox process, which takes place during thermal decomposition of [Ni(NH 3 ) 6 ](NO 3 ) 2 , determines that this decomposition may be presented as the following reactions:…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of the results of our previous investigations [20,[23][24][25][26] and taking into account the results obtained by other researchers [27][28][29][30][31][32][33][34][35][36], the redox process, which takes place during thermal decomposition of [Ni(NH 3 ) 6 ](NO 3 ) 2 , determines that this decomposition may be presented as the following reactions:…”
Section: Resultsmentioning
confidence: 99%
“…Our efforts in growing single crystals of compound 1 were not successful due to the decomposition reaction observed during the crystallization periods. Therefore, Rietveld refinement of the XRD data was performed (Figure 1) on the X‐ray crystallographic parameters of the isomorphous compound 3 5. Compound 1 crystallizes in a close packed cubic lattice of [Cd(NH 3 ) 4 ] 2+ ions, where MnO 4 – anions occupy all the octahedral and half of the tetrahedral interstices.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1 crystallizes in a close packed cubic lattice of [Cd(NH 3 ) 4 ] 2+ ions, where MnO 4 – anions occupy all the octahedral and half of the tetrahedral interstices. A comparison of its lattice parameters with the analogous values of the isostructural [Cd(NH 3 ) 4 ](ReO 4 ) 2 ( 4 )3,8 and [Zn(NH 3 ) 4 ]( X O 4 ) 2 [ X = Mn ( 2 )5 and X = Re ( 5 )3 as well as X = Cl ( 8 )9] compounds is shown in Table 1. The room‐temperature powder X‐ray diffraction studies on the perdeuterated analogue ( 1 ‐ D ) showed a lack of isotope effect of the deuterium substitution over the value of the lattice constant and the molar volume of the elementary cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations